Biomechanical evaluation of the natural abutment teeth in combined tooth-implant-supported telescopic prostheses: a three-dimensional finite element analysis. Issue 9 (4th July 2017) - Chen, Yu; Wang, Chao; Huang, Yuanding; Feng, Tianming; Zou, Huawei; Fan, Yubo
Abstract: Telescopic overdentures supported by the combination of natural teeth and implants have been thought a valuable treatment for the severely compromised partially edentulous patients. But the combination of teeth and implants involves highly complex biomechanical problems. This study is to evaluate biomechanical behaviors of the natural abutment teeth with the treatment of combined tooth-implant supported telescopic crown prostheses in mandible through 3D FEA. According to this study, the prosthetic option supported by a combination of teeth and implants and retained by double crowns could protect teeth and their periodontal support tissues acting as a rigid splint, and may be a valuable treatment option for partially edentulous patients with severely reduced remaining teeth in mandible.